Nightmare City - Klavan, Andrew; Klavan, Andrew (Nashville, Tennessee : Thomas Nelson, 2013)
As a reporter for his high school newspaper, Tom is always on the lookout for an offbeat story. But from the moment he woke up this morning, his own life has been more bizarre than any headline could ever tell. The streets of his town are suddenly empty and silent. A strange fog has drifted in from the sea and hangs over everything. And something is moving in that fog. Something evil. Something hungry. Closing in on Tom.
Keywords: Steroid abuse -- Juvenile fiction; Steroid abuse -- Fiction; Mystery fiction; Suspense fiction; Horror fiction